Effects of physical exercise associated with a diet enriched with natural antioxidants on cerebral hypoperfusion and reperfusion injury in spontaneously hypertensive rats - Lapi, Dominga; Federighi, Giuseppe; Lonardo, Maria Serena; Chiurazzi, Martina; Muscariello, Espedita; Tenore, Giancarlo; Colantuoni, Antonio; Novellino, Ettore; Scuri, Rossana (Frontiers in Physiology, 2023)
Oxidative stress is implicated in the pathogenesis of arterial hypertension. The reduction in the bioavailability of nitric oxide (NO) causes endothelial dysfunction altering the cerebral blood vessels’ functions. Physical exercise and the intake of antioxidants improve the redox state increasing the vascular NO production and/or the decrease in NO scavenging by reactive oxygen species (ROS). The present study was aimed at assessing the effects of physical exercise associated with a diet enriched with antioxidants from the Annurca apple in preventing the microvascular damage due to cerebral hypoperfusion and reperfusion injury in Spontaneously Hypertensive Rats (SHRs). The rat pial microcirculation was investigated by intravital fluorescence microscopy through a parietal closed cranial window. As expected, SHRs subjected to physical exercise or an antioxidants-ernriched diet showed a reduction of microvascular permeability, ROS formation and leukocyte adhesion to venular walls, with a major effect of the antioxidants-enriched diet, when compared to untreated SHRs. Moreover, the capillary perfusion was preserved by both treatments in comparison with untreated SHRs. Unexpectedly, the combined treatments did not induce higher effects than the single treatment. In conclusion, our results support the efficacy of physical activity or antioxidants supplement in reducing the microvascular alterations due to hypertension and ascribes to an antioxidants-enriched diet an effective microvascular protection in hypertensive SHRs.